An agent-based architecture for fast context transfers during handoffs. (16th July 2008) - Siddiqui, Farhan; Zeadally, Sherali
Multimedia applications often involve multiple media types such as voice, text, video, and graphics. Many of these applications have low delay requirements and do not perform well under large delay conditions. To provide efficient support for mobile multimedia applications as well as seamless network connectivity, it is crucial that handoff delays are minimised. In this work, we present the design, implementation, and evaluation of an architecture based on agent technology to minimise handoff delays. Our empirical results demonstrate that our proposed agent-based context transfer approach improves handoff delay performance by 54.8% compared to the traditional client/server context transfer approach which performs handoffs by exchanging multiple messages.